The Bronze Lady of Sleepy Hollow: Compounding the Hybridity of Online Legendry - Peretti, Daniel (Ethnologies, 2022)
Legend scholarship has often focused on how legend translates to behavior in the form of legend trips. This article explores how accounts of a legend trip appear in oral tradition, print culture, and in various platforms on the internet, using the example of the legend of the Bronze Lady of Sleepy Hollow Cemetery. Relying on notions of hybridity in both folklore and the study of literature, I discuss the hybridization of the legend that occurs online, leading to an analysis of the legend as it has merged the “Get Ready with Me” make-up tutorial video. Based on ethnography and the examination of digital and print texts, this analysis attempts to articulate the affordances of new media and different context for narrative.